Quality milk: A veterinarian's viewpoint - Reid, D.A. (Kansas Agricultural Experiment Station, 2012)
I would like to thank the organizers of this program for the opportunity to speak to you today on a subject that I feel is of the utmost importance to the dairy industry in the U.S. The problem to which I am referring is not the current devastating drought that has affected many of the dairy-producing areas in our country, but rather the repercussions of the dairy industry's inability to market a wholesome uncontaminated product that is viewed as such by a majority of the consumers in the U.S. I am sure that most of us here can remember the problems that occurred several years ago with contaminated Tylenol products that reached various market areas in the U.S. With the recent revelations that approximately 70% of the milk samples in several metropolitan areas, including Boston and Seattle, were contaminated with sulfamethazine, I fear that we in the dairy industry also could be faced with much more adverse publicity than what we have seen in the recent past. There has been at least one segment on 60 Minutes dealing with the potential contamination of milk products, along with articles in the Wall Street Journal. This publicity is definitely not what the dairy industry needs today. Currently, what publicity has been generated has not shaken the confidence that American consumers have in dairy products as a source of wholesome, uncontaminated, nutritional components of their diet. However, those of us that are involved in the dairy industry need to realize the potential devastation that could occur to our complete marketing system, if adulterated, contaminated milk is not removed from the market place.
Keywords: Dairy; Residue testing; Veterinarian; Quality